Afghanistan are we losing the peace? - Wisner, Frank (Frank G.); Platt, Nicholas; Boulton, Marshall M. (Council on Foreign Relations, 2003)
Report on United States foreign policy following Operation Enduring Freedom in Afghanistan, with recommendations.